2016
DOI: 10.1111/conl.12242
|View full text |Cite
|
Sign up to set email alerts
|

Managing Natural Capital Stocks for the Provision of Ecosystem Services

Abstract: Decision makers and land managers are increasingly required to manage landscapes for multiple purposes and benefits. However, despite progress in the development of frameworks linking natural capital to the provision of ecosystem services and human benefits there remains little guidance for how management interventions can improve ecosystem service provision. As ecosystem services cannot be directly influenced, interventions need to be directed toward natural capital stocks. We provide a framework that explici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 41 publications
(66 reference statements)
1
56
0
1
Order By: Relevance
“…Our typology is also consistent with the framework proposed by Maseyk et al (2017), who identify three ecological processes that underpin ecosystem services: the species-area relationship (equivalent to our group C, specific species; and B, supporting habitat); landscape ecology (group D, physical and biological diversity); and biodiversity-ecosystem function (group D, biological diversity). However our typology also identifies group A -amount of vegetation.…”
Section: Comparison With Other Studiessupporting
confidence: 86%
See 2 more Smart Citations
“…Our typology is also consistent with the framework proposed by Maseyk et al (2017), who identify three ecological processes that underpin ecosystem services: the species-area relationship (equivalent to our group C, specific species; and B, supporting habitat); landscape ecology (group D, physical and biological diversity); and biodiversity-ecosystem function (group D, biological diversity). However our typology also identifies group A -amount of vegetation.…”
Section: Comparison With Other Studiessupporting
confidence: 86%
“…To assist with this, Maseyk et al (2017) suggested dividing the attributes of natural capital (soils and vegetation) into manageable and unmanageable attributes, so that management strategies can focus on the manageable attributes. The review of potential interactions between services (Section 3.3) can help to inform the development of management strategies to maximise synergies and minimise undesirable trade-offs.…”
Section: Informing Management Decisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A common goal of ecosystem services research is to understand how we can increase the overall delivery and diversity of ecosystem services produced from different landscapes (environmental spaces). In particular, for the ecosystem services framework to translate into practical land management, decision‐makers must have the tools to understand how land use affects the delivery of different ecosystem services in order to decide what to prioritise or how to achieve the best compromise (De Groot, Alkemade, Braat, Hein, & Willemen, ; Martinez‐Harms et al., ; Maseyk, Mackay, Possingham, Dominati, & Buckley, ). For cultural ecosystem services, this is complicated by the fact that they are influenced by many factors, such as natural landscape features, heritage and history, current land management practices, and how people interact with the environment (Church et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In these situations the target biota to be offset would be identified through a ecosystem services lens rather than a purely conservation lens. Thus, the biodiversity elements entered into the model would be those stocks of natural capital that are known to contribute to the provision of required ecosystem services and that are also responsive to offset actions (Maseyk et al 2016).…”
Section: Introductionmentioning
confidence: 99%